Incidence of Bacteriobilia and the Correlation with Antibioticoprophylaxis in Low-Risk Patients Submitted to Elective Videolaparoscopic Cholecystectomy: A Randomized Clinical Trial - Marcos Alberto Pagani; Pedro Meira Dolfini; Beatriz Flávia de Moraes Trazzi; Maria Ines Meira Dolfini; William Saranholi da Silva; Eduardo Federighi Baisi Chagas; Carlos Henrique Bertoni Reis; João Paulo Galletti Pilon; Bruna Trazzi Pagani; Rodrigo Tavore Strasser; Claudemir Gregório Mendes; Fausto Tucunduva Vernaschi; et al. (MDPI AG, 2023)
Cholelithiasis has a major impact on global health and affects an average of 20% of the Western population. The main risk factors are females, age over 40 years, obesity and pregnancy. Most of the time it is asymptomatic, but when there are symptoms, they are generally nonspecific. Bile was considered sterile, but today it is known that it contains a complex bacterial flora, which causes biofilm in the gallbladder and gallstones. Among the main bacteria associated with cholelithiasis are Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae, species of Enterococcus spp. and Acinetobacter spp. Antibiotic prophylaxis is used in an attempt to reduce postoperative infections, especially at the surgical site. However, some authors found no relationship between the use of antibiotic prophylaxis and a lower risk of surgical site infection. Thus, the aim of this double-blind randomized clinical trial was to compare the existence or not of bacteriobilia in patients at low anesthetic risk who underwent videolaparoscopic cholecystectomy, and its correlation with the use of prophylactic antibiotics. This study included 40 patients between 18 and 65 years old, diagnosed with cholelithiasis, symptomatic or not, with low anesthetic risk classified by the American Society of Anesthesiology in ASA I or ASA II, without complications or previous manipulation of the bile duct, who underwent elective video cholecystectomy, divided into two groups: Experimental Group A (n = 20), which received 2 g of Cephalotin (first-generation Cephalosporin, Keflin®, ABL antibiotics, Cosmópolis, Brazil) during anesthetic induction, and Control Group B (n = 20), where no antibiotics were administered until bile collection. After the procedure, a bile sample was collected and culture and antibiogram were performed. In the sample, 22 (55%) were classified as ASA I and 18 (45%) as ASA II. It was observed that 81.8% of the patients who had a positive culture did not use antibiotics, against 18.2% of those who used prophylaxis. When comparing patients regarding anesthetic risk, ASA I patients had a positive culture in 9.1% of cases, against 90.9% in patients classified as ASA II. It was concluded that patients with higher anesthetic risk (ASA II) have a higher chance of bacteriobilia and benefit from antibiotic prophylaxis when compared to patients with lower anesthetic risk (ASA I).